The Development of Mathematical Learning Materials Based on Problem-Based Learning to Enhance Problem-Solving Ability at Senior High School - Erliza, Refni; Permana, Dony; Fauzan, Ahmad; Syarifuddin, Hendra (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
The research aims to produce a mathematics learning tool based on problem-based learning to improve problem-solving abilities in semester II class XI high school material that is valid, practical, and effective. This type of research is development research, while the population in this research is class XI students at SMAN 4 Payakumbuh using a random sampling technique class. This research uses a development model consisting of 3 stages: the initial investigation stage, the development or prototyping stage, and the assessment stage. Data collection techniques in this development model are interviews with teachers and students and questionnaires for teachers and students. The validation test stage consists of self-evaluation and validation sheets for the RPP and LKPD. Practicality test instruments describe the practicality of the learning tools being developed. The research results showed that the lesson plans developed averaged 3.56 in the very valid category. In contrast, the LKPD developed had an average of 3.39 in the very valid category. Overall, the practicality value of the RPP is 87.50% with very practical criteria, and the practicality value of LKPD is 88.67% with very practical criteria. This means that based on the questionnaire on the practicality of the RPP and LKPD filled out by educators for mathematics learning tools using the PBL model, it is stated that they are very practical and can be used well by students in learning.